1992
DOI: 10.1148/radiology.185.2.1410365
|View full text |Cite
|
Sign up to set email alerts
|

Common carotid artery bifurcation: evaluation with spiral CT. Work in progress.

Abstract: To determine the utility of spiral computed tomography (CT) in evaluation of carotid artery stenosis, spiral CT images of 20 patients were compared with images obtained with conventional angiography (20 patients), ultrasound (US) (15 patients), and magnetic resonance (MR) angiography (six patients). The category of stenosis was determined for each internal carotid artery on the basis of the percentage of narrowing: mild = less than 30%, moderate = 30%-69%, and severe = 70%-99%. Occlusions were also noted. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
2
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(40 citation statements)
references
References 0 publications
1
35
2
2
Order By: Relevance
“…However, very small ulcerations can still be obscured by any of these artifacts. In particular, we agree with other authors 42,45 that calcified plaque is the major limitation of CTA in studying plaque morphology and detecting ulcerations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, very small ulcerations can still be obscured by any of these artifacts. In particular, we agree with other authors 42,45 that calcified plaque is the major limitation of CTA in studying plaque morphology and detecting ulcerations.…”
Section: Discussionsupporting
confidence: 93%
“…24 We demonstrated that MDCTA has a very a high sensitivity (93.75%) and specificity in detecting carotid artery plaque ulcerations. The sensitivity that we reported is higher compared with the works of Link et al, 41 Schwartz et al, 42 Debernardi et al, 24 Oliver et al, 10 and Walker et al 18 ; in these works, however, single-section CT scanners were used. We performed CTA examinations with a multidetector row scanner, and we studied each examination with axial and multiple postprocessed reconstructed images (MIP, MPR, SSD, and VR).…”
Section: Discussioncontrasting
confidence: 63%
“…CT has been found in multiple trials to be accurate in the diagnosis of carotid artery stenosis but can lead to miscategorization of the degree of stenosis, especially if not performed and evaluated properly or if the plaques causing stenosis are heavily calcified [8][9][10][11][12][13]. However, our groups for classification of the percentage luminal stenosis for total vessel and individual vessel scores were relatively broad, making error in categorization less likely.…”
Section: Discussionmentioning
confidence: 94%
“…This may partly be because of the predominant use of sonography and MR angiography in imaging studies involving the neck vasculature, but these techniques are significantly limited in the evaluation of calcium. MDCT angiography is a robust technique for assessing calcification and can potentially depict and allow quantification of load in the carotid arteries in a manner similar to coronary artery scoring, while being highly accurate for measuring luminal stenosis [8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…The different MR modalities that may be used for assessment include T 1 -and, T 2 -weighted images, MR angiograms, and functional MR imaging: all of these help to complete the initial diagnosis and aid planning of the surgical approach and subsequent patient management. The increased use of three-dimensional (3-D) image reconstruction methods [1,15,17,18,22,23,27] and surgical navigators [2,3,8,12,16,26,[30][31][32] has resulted in a substantial changes in the practice of neurosurgery. We have developed a protocol for the use of 3-D reconstructions that combines these modalities into one comprehensive model, which is then used for surgical planning and intraoperative navigation.…”
Section: Abstract * Low-grade Glioma * Three-dimensional Reconstructmentioning
confidence: 99%